Pengukuran Kinerja Efisiensi Perbankan Syariah: Analisis Empiris 15 Bank Syariah di Indonesia 2005-2007 - Endri, Endri (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
Using the non-parametric method of Data Envelopment Analysis (DEA) and the parametric method of Stochastic Frontier Approach (SFA). this study investigates the efficiency of the Islamic Banking recent operations in Indonesia over the period 2005 to 2007. In specifying input-output variables of Islamic banks, the intermediation approach is selected as it is in line with the principle of Islamic financial system. The attributions of technical efficiency (utilization of capacity) and scale efficiency (optimality of scale achieved) are identified. The principal findings for the period under study indicated that technical and scale efficiency scores are improving but n'bt 100 percent optimal during research period. According to SFA approach, closer to100 percent meansa bank actsefficiently. Overall, the result shows that Islamic banks suffer slight inefficiencies during the period 2005-2007, and tend to be increasing. The study has several important policy implications to offer, one of which is that it could be taken as a guideline for the Indonesian government to chart a policy on banking deregulation and mergers. Moreover, the study provides some information and identifies the source of inefficiency, which could, in turn, be used to assist banks' managements to overcome the problems of inefficiency.